Examining Human Resource Management: A Qualitative Study of Psychological Elements and Strategic Approaches with Literature Review - Imran, Un Dini; Hesti, Hesti; Ratika, Ratika (YUME : Journal of Management, 2024)
This qualitative study explores the intricate relationship between psychological elements and strategic Human Resource Management (HRM) practices in shaping organizational effectiveness. Through an extensive literature review, key themes of employee engagement, motivation, and well-being are examined within the context of HRM. The analysis draws from theories such as social exchange theory, self-determination theory, and positive organizational behavior to elucidate the mechanisms driving employee behavior and attitudes. Strategic HRM practices, characterized by high-performance work systems and employee involvement, are also investigated for their impact on organizational outcomes. Findings underscore the significance of integrating psychological elements into HRM strategies, highlighting their role in fostering employee engagement, motivation, and well-being. The study emphasizes the importance of aligning HR practices with organizational goals and values to enhance employee satisfaction, retention, and performance. Moreover, the implications for HR practitioners and organizational leaders are discussed, emphasizing the need for a proactive approach to HRM that embraces innovation, flexibility, and agility. The study calls for future research to delve deeper into emerging trends and challenges in HRM, such as the influence of technology, remote work arrangements, and innovative HRM strategies, to inform evidence-based practices and promote organizational success. Keyword: Human Resource Management; Employee Engagement; Motivation, well-being, organizational effectiveness.